Detection of Opportunistic Intestinal Protozoans in The Feces of Orphanage Children in Pekanbaru (Nusantara Science and Technology Proceedings, 2022)
Opportunistic intestinal protozoa are intestinal protozoa that can infect humans and cause clinical symptoms depending on the patient’s immune status. In immunocompromised patients, infection by opportunistic intestinal protozoa can cause symptoms of diarrhea; mild to severe diarrhea. In addition to immunocompromised patients, these opportunistic intestinal protozoa can also be found in children with poor personal hygiene and environmental sanitation. This research was a descriptive study that aims to determine the incidence of opportunistic intestinal protozoa infection in orphanage children in Pekanbaru, which was conducted from August until October 2022. The result of microscopic examination with acid-fast staining were 70 samples of children’s feces from 8 of the orphanage found 41,4% were positive for opportunistic intestinal protozoans; consisting of 11.4% Cryptosporidium sp. infection, Blastocystis hominis as much as 21.4%, Cyclospora sp as much as 1.4%. and mixed infections of Blastocystis hominis and Cryptosporidium sp. as much as 7.2%. The prevalence of opportunistic intestinal protozoa found in the feces of orphanage children in Pekanbaru is high, but to our knowledge, these intestinal protozoans will not cause definite symptoms as long as the individual’s immune status is good.